Comparison of NIRS exercise intensity thresholds with maximal lactate steady state, critical power and rowing performance - Leonardo Trevisol Possamai; Fernando Klitzke Borszcz; Rafael Alves de Aguiar; Ricardo Dantas de Lucas; Tiago Turnes (Termedia Publishing House, 2023)
This study aimed to compare the intensity of deoxygenated haemoglobin concentration ([HHb]) and tissue saturation index (TSI) breakpoints ([HHb]-BP and TSI-BP) with maximal lactate steady state (MLSS)and critical power (CP), and to describe their association with2000-m rowing ergometer performance. Fourteen male rowers performed on a rowing ergometer: I) a discontinuous incremental test with 3-min stages (INC 3 ); II) a continuous incremental test with 1-min stages (INC 1 ); III) constant workload tests to determine MLSS; and IV) performance tests of 500 m, 1000 m, 2000 m and 6000 m to determine CP. CP (257±39 W; 3.79±4.1 L·min −1 ) was higher than [HHb]-BP 3 (205±26 W; 3.48±2.9 L·min −1 ), [HHb]-BP 1 (207±27 W; 3.27±3.2 L·min −1 ), and TSI-BP 3 (218±31 W; 3.51±3.0 L·min −1 ), but not higher than TSI-BP 1 (222±34 W; 3.43±3.2 L·min −1 ). MLSS (187±26 W; 3.33±3.2 L·min −1 ) was lower than TSI-BP 3 and TSI-BP 1 for power output, but not different in any comparison for V̇ O 2 . The limits of agreement for power output and V̇ O 2 suggest poor agreement among these thresholds. The low level of agreement compromises the use of [HHb]-BP and TSI-BP for estimating MLSS and CP; therefore, these thresholds should not be considered interchangeable.